Rancang Bangun Sistem Informasi Akademik Fakultas Matematika Dan Ilmu Pengetahuan Alam Berbasis Website - Amazon, Firlo; Widiatry, Widiatry; Pranatawijaya, Viktor Handrianus (Universitas Palangka Raya, 2021)
A website based academic information system is indispensable for processing academic data such as processing data on subjects, grades, filling study plan cards, thus supporting the achievement of the vision, mission and academic goals of the Faculty of Mathematics and Natural Sciences, one of which is to provide education by optimizing the use of Information and Communication. Technology (ICT) for academic services. In designing the Academic Information System for the Faculty of Mathematics and Natural Sciences, this Website-Based uses the waterfall method with stages, Requirements Definition, System and Software Design, Implementation and Unit Testing, Integration and System Testing, Operation and Maintenance. The software used in building this website is Visual Studio Code, MySQL, and XAMPP. This website has been tested with blackbox testing which results that the features on the website can run well. Website-Based Design of Academic Information Systems for the Faculty of Mathematics and Natural Sciences This website was developed as an information medium that facilitates information such as study plan card data, study result cards, and class schedules that can facilitate lecturers and students in seeing the academic activities they carry out.